Islamic Religious Education Based On Local Culture: Strategy For Developing Islamic Religious Education Materials In Madrasah Ibtidaiyah - Zumzianah; Usman; Wahab (IJGIE (International Journal of Graduate of Islamic Education), 2024)
Islamic religious education in Indonesia is very important in shaping the character and morals of students, but it needs to be more integrated with local cultural values. This research aims to develop a strategy for developing Islamic Religious Education materials based on local culture at Madrasah Ibtidaiyah. The research method used is descriptive research with a qualitative approach. Data collection was carried out through literature studies, observations, and interviews with experts in Islamic Religious Education and local culture. Data analysis uses content analysis content. The research results show that integrating local cultural values in Islamic Religious Education materials can increase students' understanding and involvement in learning about the Islamic religion. Material development strategies include identification of local cultural values, preparation of material based on local stories, teacher training in using the material, and regular evaluation and improvement. This research means that there is a practical guide for Islamic religious education teachers to develop material that is relevant to the local cultural context so that it can increase the effectiveness of Islamic spiritual learning at Madrasah Ibtidaiyah.